Impact sound attenuation of subfloor mortars made with exfoliated vermiculite and chrome sawdust. (March 2021) - Führ, Guilherme; Masuero, Angela B.; Pagnussat, Daniel T.; Menna Barreto, Maria Fernanda F.
Abstract: Acoustic performance is a building and users requirement, sometimes neglected, which commonly causes discomfort to the neighborhood. Subfloors with acoustic insulation properties are an alternative to minimize this problem. They are made with different materials types, including industrial wastes, reducing the Construction Industry impact, making it more sustainable. This research aims at assessing, experimentally, different subfloor mortars, with lightweight aggregates, to reduce impact sound, produced from the replacement of different contents of natural aggregate for exfoliated vermiculite and chrome sawdust (waste from tanning industries), in comparison with an industrialized mortar commercialized with acoustic isolation characteristics. The mortars were characterized by national standards, their dynamic stiffness was measured (according to ISO 9052-1) and used to estimate the sound reduction for impact noise (as stated by ISO 12354). Mortars with aggregate substitutions, including the wastes in higher substitution contents, have the potential to become an alternative for impact noises insulation in floating floor systems.